Effect of moisture ventilation and multi-drying shelf on drying perfor-mance of round scads (Decapterus maraudsi, Temminck & Schlegel) - Jareanjit, Jaruwat; Jeentada, Wasan (Asia-Pacific Journal of Science and Technology, 2017)
This research is to study how factors of moisture ventilation openings and drying tray configurations affect the drying performance of Round scads (Decapterus maraudsi, Temminck & Schlegel). The performance of multi-tray dryer and solar moisture distillation combined with radiation reflecting sheets was compared with that of a natural drying method in a fresh marine fish process. The moisture of products was reduced in a passive greenhouse dryer covered with a glass slanted at an angle of 12บand a transparent acrylic sheet size of 83 x 75 x 100 cm 3 . The drying cabinet was composed of 5 shelves each of which was used for drying one kilogram of split-back fresh Round scads. A gutter was placed to receive the condensed moisture from the front and the top pieces of glass and vented outside the drying cabinet. The experiment was conducted in 3 cases, namely a closed drying cabinet, an open drying cabinet and a closed drying cabinet with moisture ventilation top and bottom openings of the back cover of the cabinet. The performance of shelf configurations in drying the fish was examined the variables of moisture content and drying rate to produce physical feature of products to serve the market demand (natural drying method). The temperature and weight on each drying shelf was recorded during a period of 09:00 am. - 03:00 pm. The result indicates that a drying performance in a closed drying cabinet with moisture ventilation top and bottom openings of the back cover of the cabinet with a combination of a drying shelf configurations or proper shelf substitution could reduce the initial moisture of the fish in each shelf from approximately 308%(d.b.) to approximately 134-153% (d.b.), which was lower than the reduced moisture of the fish dried in a natural drying method of approximately 155%(d.b.). This case helped solve the problem of temperature separation in a multi-shelf drying cabinet. It also made the moisture and physical feature of products in each shelf similar and met the demand of the market. Moreover, the duration of product drying was less than 6 hours varying with solar radiation values. The design of the multi-shelf drying cabinet provided clean and sanitary products and 3-fold decrease in drying area.